Green Plasma Has a Superior Hemostatic Profile Compared With Standard Color Plasma. Issue 8 (August 2022) - Kalkwarf, Kyle J.; Cardenas, Jessica C.; Wade, Charles E.; Cotton, Bryan A.
Background: Limitations in available donors have dramatically reduced plasma availability over the past several decades, concurrent with increasing demand for some types of plasma. Plasma from female donors who are pregnant or taking oral contraceptives often has a green appearance, which frequently results in these units being discarded. This pilot study aimed to evaluate the hemostatic potential of green compared to standard-color plasma. Materials and Methods: Plasma from twelve blood group-matched female and twelve male donors was obtained from the local blood center. Six of the female and all of the male units of plasma had a normal appearance (STANDARD), while six of the female units were grossly green (GREEN). The hemostatic potential was evaluated by thrombelastography (TEG), calibrated automated thrombogram (CAT), and coagulation factor level measurements. Univariate analysis was performed using Wilcoxon Rank-Sum. Results: GREEN plasma was more procoagulant for all TEG values ( r -value, k-time, angle, mA) when compared to STANDARD plasma. Differences were also observed in coagulation factor levels, with GREEN plasma having higher than STANDARD (factors II; VII, IX; X, XI, Protein S, and plasminogen); conversely, GREEN plasma had a longer lag time in CAT. Discussion: This pilot study demonstrates that female donors with green plasma have a superior hemostatic profile than standard plasma. GREEN plasma should be further investigated for its safety profile and hemostatic potential, so if it is found to be a safe and functionally non-inferior product, it should be actively re-introduced for transfusion in bleeding patients.